Efficiency Power Plant Implementation Decision-Making Based on the Profit Function and Its Numerical Simulation - Zhu, Yiping; Jin, Yue (Frontiers in Energy Research, 2021)
The efficiency power plant (EPP) is a kind of virtual power plants with zero emission, zero pollution and low cost, and is a high-quality low-carbon production behavior for input-output analysis. In the process of implementing EPP, enterprises not only save electricity, but also reduce carbon emissions, while meanwhile increase the cost of R&D and equipment. Therefore, it is very necessary to study relationships between carbon quota and EPP implementation decision. In this paper, we build the profit functions of three different types of enterprises implementing EPP and analyze the relationship of main parameters, such as the probability of implement EPP, electricity saving, income, cost and carbon quota, and obtain 9 relative results. Then we use 'Maple' software to simulate the results by drawing images of parameters and all the above 9 results passed the simulation test verify. At last, we collect the actual survey data and use vc++ programming to carry out an empirical study in China to prove the practicability of the model and the results. The results show that under the carbon quota trading system, enterprises should tend to implement EPPs, and increase investment in R&D and acquisition of EPPs, and need to adjust the intensity of implementing EPPs according to the change of carbon quota, unit carbon quota income, to obtain higher income.